The effects of male age on sperm DNA damage in an infertile population - Vagnini, Laura; Baruffi, R. L R; Mauri, A. L. [UNESP]; Petersen, C. G. [UNESP]; Massaro, F. C.; Pontes, Anaglória [UNESP]; Oliveira, J. B A; Franco, J. G. [UNESP] (Elsevier, 2007)
The objective was to investigate the influence of age on sperm DNA damage. Semen samples were collected from 508 men in an unselected group of couples attending infertility investigation and treatment. DNA fragmentation in spermatozoa was measured by TdT (terminal deoxynucleotidyl transferase)-mediated dUTP nick-end labelling (TUNEL) assay; at least 200 spermatozoa in randomly selected areas of microscope slides were evaluated using a fluorescent microscope and the percentage of TUNEL positive spermatozoa was determined. The number of cells with red fluorescence (TUNEL positive) was expressed as a percentage of the total sample [DNA fragmentation index (DFI)]. Age was treated as a continuous variable for regression and correlation analysis. The following male age groups were used: Group I: ≤35 years, Group II: 36-39 years, and Group III: ≥40 years. DFI was significantly lower in Group I than in Group II (P = 0.034) or III (P = 0.022). There was no difference in DFI between Groups II and III. In addition, regression analysis demonstrated a significant increase in sperm DFI with age (P = 0.02). TUNEL assay clearly demonstrates an increase in sperm DNA damage with age. © 2007 Published by Reproductive Healthcare Ltd.
Keywords: Age; DNA damage; Male infertility; Spermatozoa; TUNEL; DNA; DNA fragment; adult; age; asthenospermia; controlled study; correlation analysis; fluorescence microscopy; human; major clinical study; male; male infertility; nick end labeling; oligospermia; regression analysis; semen analysis; spermatozoon; Adult; Aged; Aging; DNA Damage; Humans; In Situ Nick-End Labeling; Infertility, Male; Male; Middle Aged